2014
DOI: 10.1186/1471-2369-15-95
|View full text |Cite
|
Sign up to set email alerts
|

What is the real impact of acute kidney injury?

Abstract: BackgroundAcute kidney injury (AKI) is a common clinical problem. Studies have documented the incidence of AKI in a variety of populations but to date we do not believe the real incidence of AKI has been accurately documented in a district general hospital setting.The aim here was to describe the detected incidence of AKI in a typical general hospital setting in an unselected population, and describe associated short and long-term outcomes.MethodsA retrospective observational database study from secondary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 27 publications
2
54
0
4
Order By: Relevance
“…This has stark clinical and financial implications, especially if it is confirmed that the prevalence and incidence of CA‐AKI truly exceeds HA‐AKI. The economic burden of HA‐AKI has been well described . Using the current evidence, it will be important to estimate the economic burden imposed by CA‐AKI and allocate resources accordingly.…”
Section: Epidemiologymentioning
confidence: 99%
“…This has stark clinical and financial implications, especially if it is confirmed that the prevalence and incidence of CA‐AKI truly exceeds HA‐AKI. The economic burden of HA‐AKI has been well described . Using the current evidence, it will be important to estimate the economic burden imposed by CA‐AKI and allocate resources accordingly.…”
Section: Epidemiologymentioning
confidence: 99%
“…Acute kidney injury (AKI) occurs in 1 in 7 hospital admissions 1 . Even those with small increases in creatinine levels have 4-fold greater hospital mortality than those with no creatinine level increase 2 .…”
mentioning
confidence: 99%
“…Some of these risk factors are common between CKD and AKI, and they included metabolic syndrome, obesity, proteinuria, HTN, and vascular abnormalities. These comorbidities can also play a role in the development of CKD following AKI [21,41] . On the other hand, there is an established association between OSA and the above-named chronic conditions.…”
Section: Discussionmentioning
confidence: 99%